2020
DOI: 10.1186/s12881-020-0968-7
|View full text |Cite
|
Sign up to set email alerts
|

Salivary epigenetic biomarkers as predictors of emerging childhood obesity

Abstract: Background: Epigenetics could facilitate greater understanding of disparities in the emergence of childhood obesity. While blood is a common tissue used in human epigenetic studies, saliva is a promising tissue. Our prior findings in non-obese preschool-aged Hispanic children identified 17 CpG dinucleotides for which differential methylation in saliva at baseline was associated with maternal obesity status. The current study investigated to what extent baseline DNA methylation in salivary samples in these 3-5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 59 publications
(41 reference statements)
2
13
0
Order By: Relevance
“…Interestingly, the influence of FTO gene variant on adiposity appears to be small in infancy but strengthens considerably during childhood [ 38 ]. These results may be reconciled with our results and previous studies which have shown association between adiposity and DNA methylation in older children which include studies of both blood [ 39 , 40 ] and saliva samples [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the influence of FTO gene variant on adiposity appears to be small in infancy but strengthens considerably during childhood [ 38 ]. These results may be reconciled with our results and previous studies which have shown association between adiposity and DNA methylation in older children which include studies of both blood [ 39 , 40 ] and saliva samples [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 89%
“…It should be mentioned that the correlation between blood and saliva DNA methylation has not always been reported, due to the high variability in individual cellular composition, even at different time points [73], overall affecting the proportion of white blood cells and buccal keratinocytes [74,75]. However, the use of saliva samples to evaluate DNA methylation as biomarker has been already suggested, for example, for borderline personality disorder [76], schizophrenia [77], stress [78] or as a predictor of childhood obesity [79]. In terms of epigenetic modifications, it has been reported that there is higher correlation between saliva and brain tissues when compared to brain and blood [80].…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic changes are produced in these new generations, such as modifications in gene promoters involved in stress and appetite regulation (Schneeberger et al, 2012;Schroeder et al, 2017). Moreover, early adverse childhood experiences could cause DNA methylations in genes associated with obesity (Kaufman et al, 2018;Rushing et al, 2020).…”
Section: Wd and Stressmentioning
confidence: 99%